Review of the Genus Orygocera Walsingham, 1897 from the Mascarenes with description of a new species (Lepidoptera: Depressariidae, Stenomatinae) - Bippus, M. (SHILAP Revista de lepidopterología, 2020)
The species of the genus Orygocera Walsingham, 1897 in the Mascarene islands are reviewed. One new species Orygocera albanix Bippus, sp. n. is described. One subspecies, Orygocera amphitricha reunionensis Viette, 1991 is found to be a junior synonym of the nominal species Orygocera amphitricha amphitricha (Meyrick, 1910). Hostplants are recorded for one species and larval stages are illustrated for the first time of this genus.